An Analysis of Elective English Students' Ability in Writing Fairy Tales at SMAN 1 Lareh Sago Halaban - Annisa, Annisa; Sari, Senorica Yulia (Journal of English Language Teaching, 2024)
The purpose of this study is to find out the students ability in writing fairy tales in terms of content, organization, vocabulary, language features, and mechanics. In this research, the researcher used a quantitative research. The researcher chose the design because the researcher wants to analyze the elective English students’ ability in writing fairy tales at SMAN 1 Lareh Sago Halaban. The instrument used in this a research was writing test. The population of this study was 207 elective English students; the sample of the writing test was 36 students. The sample of this research was chosen by using cluster random sampling. Writing test was used to find out the students ability in writing fairy tales, especially in the aspect of content, organization, vocabulary, language features, and mechanics.  Data were analyzed by combining Weigle's assessment theory and Harris's writing scale. The result of this research was show that average scores of the student's writing test were 74,30. It means that the ability of the students were in the "Good" level. More specifically, in the aspects of content, organization, vocabulary and language features, the students are at the "Good to average" level, but in the mechanics aspect the students are at the "Fair to poor" level.